2015
DOI: 10.1590/0034-737x201562030007
|View full text |Cite
|
Sign up to set email alerts
|

Consorciação taro e crotalária manejada com corte rente ao solo e poda na altura do dossel

Abstract: A associação de culturas com leguminosas de adubação verde visa à manutenção ou melhorias da fertilidade do solo. Com o objetivo de avaliar a consorciação do taro 'Japonês' com crotalária, foram conduzidos dois experimentos, em Viçosa, MG, no período de 10/09/2010 a 10/06/2011. No Experimento I, as plantas de crotalária foram cortadas rente ao solo e, no Experimento II, podadas à altura do dossel do taro; em ambos, os tratamentos consistiram em seis épocas de corte ou poda da crotalária (75; 105; 135; 165; 195… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 7 publications
(17 reference statements)
2
6
0
6
Order By: Relevance
“…These authors demonstrated that if farmers wanted to harvest green manure at the blooming period, as commonly recommended, it would be possible to perform two cuts before harvesting, thus increasing organic material production. Furthermore, Puiatti et al (2015) observed that larger quantities of fresh and dry phytomass, as well as carbon and nutrients are provided by crotalaria cut or thinned at 135 and 165 days after sowing, reporting yields of 21.0 and 15.25 t.ha -1 , respectively. Corroborating these results, the highest mean for SFB (23.8 t.ha -1 ) was obtained in treatments where both thinnings occurred within 30-day interval, highlighting it as the best span for achievement great C. juncea shoot fresh biomass yield in the study area.…”
Section: Resultsmentioning
confidence: 99%
“…These authors demonstrated that if farmers wanted to harvest green manure at the blooming period, as commonly recommended, it would be possible to perform two cuts before harvesting, thus increasing organic material production. Furthermore, Puiatti et al (2015) observed that larger quantities of fresh and dry phytomass, as well as carbon and nutrients are provided by crotalaria cut or thinned at 135 and 165 days after sowing, reporting yields of 21.0 and 15.25 t.ha -1 , respectively. Corroborating these results, the highest mean for SFB (23.8 t.ha -1 ) was obtained in treatments where both thinnings occurred within 30-day interval, highlighting it as the best span for achievement great C. juncea shoot fresh biomass yield in the study area.…”
Section: Resultsmentioning
confidence: 99%
“…No caso da pequena propriedade agrícola, normalmente caracterizada pela exploração de cunho familiar, associa-se a esses a restrição de área física para os cultivos. Para situações dessa natureza, a consorciação de culturas torna-se uma opção interessante (Puiatti et al, 2015).…”
Section: Introductionunclassified
“…Portanto, o ambiente com maior restrição de luz (sombrite® 50%) proporcionou maior crescimento em altura das plantas de taioba. Esse comportamento também foi observado em plantas de taro (Colocasia esculenta), uma planta também da família Araceae, quando submetido à restrição de luz em cultivo em consórcio com crotalária (Puiatti et al, 2015) ou sob telas, devido ao alongamento do pecíolo (Gondim et al 2007;2008), além de apresentarem maior produção de biomassa da parte aérea (Gondim et al, 2007).…”
Section: Resultsunclassified